The Outcome Analysis of Cesarean Section Cases in One-Year Period - Balcı, Osman; Gezginç, Kazım; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: The purpose of the study is to evaluate the rates, indications and complications of patients who had undergone cesarean section in one year, in the department of obstetrics and gynecology Selçuk Univercity, Meram Medical Faculty. STUDY DESIGN: Patients who gave birth between january 2005 and january 2006 in our hospital were enrolled in this study and retrospectively analized. The cesarean section rates, its complications, indications, the patients mortality and morbidity were studied. RESULTS: The total number of births in one year was 2148. Of these 2148 births, 1055 (49.11%) were vaginal births and the remaining 1093 (50.88%) were cesarean deliveries. Although prior cesarean deliveries were the major indication with 402 (36.77%) cases, fetal distress with 144 (13.17%) cases, elective cesarean with 124 (11.34%), abnormal pelvis (CPD) with 108 (9.88%) cases were also found to be high. Two cases of maternal mortality were detected in our study. (18.29/10000). Of these two mortalities, one was HELLP Syndrome and the other one was preeclampsia patients. The morbidity rate was found to be 14%. 11% febrile morbidity, 1.28% postoperative endometritis, 1.09% urinary tract infection, 0.73% wound infection were detected. One patient had urinary bladder injury during surgery. CONCLUSIONS: The rates of cesarean deliveries are increasing day by day. The increased rates of prior cesarean deliveries is a critical factor for the risks of recurrent surgeries and cost-effectiveness. We concluded that to determine the real indications for primary cesarean deliveries and to be more selective and careful are assumed to decrease the cesarean delivery rates.